(untitled) (Rudarsko-geološko-naftni zbornik, 2020)
Raša coal, mined on the Istrian Peninsula (NW Croatia) for nearly 400 years up to 1999, is notable for having superhigh organic sulfur, and high levels of selenium, uranium, vanadium, and molybdenum. Selenium is the poison responsible for the widespread loss of cattle and sheep. It is essential to human health in trace amounts, but higher concentrations can be harmful. An estimated 4.4Mt. of coal remains underground within marine carbonate rocks. The study area belongs to the coastal karst of the Adriatic Sea. Several abandoned coal-mine discharges (CMDs) were released into local streams and the Raša Bay for decades. Therefore, the water quality of a natural karst spring (Fonte Gaja), the Raša Bay seawater, municipal wastewater, and the Raša CMDs were investigated, focusing on sulfur, selected metal(loid)s (major, minor, and trace), radioactivity, and cytotoxicity. The Fonte Gaja spring water, unrelated to the Raša CMD, served as a reference. Its values of Se, U, V, and Mo (µg/L) were as follows: 1.09, 0.75, 1.37, and 2.04, respectively. However, the respective levels (µg/L) were increased in the rest of the water samples as follows: 10.9, 10.8, 4.60, and 33.1. Water sulfate levels were low though. Total beta activities of the CMDs and Raša Bay water were 235 and 1320 Bq/m3, respectively, below the guideline level of 2000 Bq/m3. The cytotoxicity of water samples on the RTG-2 fish cells was not statistically significant. The large volumes of water involved mean the transport of rather large amounts of Se and U, and their deposition in the Adriatic Sea. Due to the complexity of the karst hydrogeology, knowledge of Se and U circulation patterns is highly needed.